The Filipino business leader in the time of the (COVID-19) pandemic within the lens of the Catholic social teachings - Pabalan, Joanne Marie Grace P. (Animo Repository, 2021)
The COVID-19 pandemic is not only a global health problem—its ramifications are complex and extensive. From social routines to religious gatherings, as well as economic conditions, have all been significantly affected. The global economy has entered into a recession and local establishments, especially small and medium enterprises, have not been spared. Most of these businesses have laid off workers and closed shops and stores. Within this chaos of business restructuring and systemic changes are complications and implications to the meaning of ethical business leadership and the value of work. This paper looks at these shifts and turns taking place in enterprises and workplaces in light of Catholic Social Thought (CST) and explores how these data and narratives from the ground could have contributed to a renewed or reshaped ethical identity of a Filipino business leader in the time of the (COVID-19) pandemic.